Analisis Strategi Pemasaran Produk Cicil Emas di Tengah Fluktuasi Harga: Studi Kasus BSI KCP Kejuruan Muda - Zuhrinal M. Nawawi; Yusliani Yusliani (Journal Economic Excellence Ibnu Sina, 2025)
This study uses a qualitative method with a case study approach to analyze the marketing strategy of the Cicil Emas (Gold Installment) product amid price fluctuations, as implemented by BSI KCP Kejuruan Muda. Cicil Emas is one of the flagship products of Islamic banks, offering great potential to fulfill the investment needs of Muslim communities. However, global gold price volatility poses a significant challenge in maintaining customer interest. This research aims to explore how marketing strategies are designed and applied in a dynamic market environment. Data were collected through in-depth interviews with marketing staff, direct observation, and internal documentation. The results reveal that BSI KCP Kejuruan Muda adopts adaptive marketing strategies through customer education, competitive margin offers, enhancement of digital services, and personalized approaches via Islamic finance communities. These strategies have proven effective in retaining customer loyalty and increasing the transaction volume of the Cicil Emas product despite price fluctuations. The study concludes that innovation and trust are essential in marketing Sharia-based products, particularly those that are highly sensitive to global market changes such as gold.